Faculty of language, functional models, and mechanisms - Skidelsky, Liza (2013)
In a recent series of papers, John Collins has challenged the dominant epistemic view of Chomsky’s faculty of language (FL), which holds that the FL consists fundamentally of propositional knowledge. Collins presents the architectural view that holds that the FL is a computational information-processing system. I fully endorse this broad architectural perspective. Nonetheless, I would like to discuss one aspect of his architectural view which maintains that we should not understand the FL as a causal mechanism, that is, as part of a causal nexus. In this paper, I will try to develop the main lines of an alternative,though perhaps broadly compatible, way of unfolding the architectural perspective in which it makes sense to think of an aspect of the minimalist program as a cognitive functional model that nevertheless describes a causal mechanism. I will argue that there are no compelling reasons to discard the possibility of conceiving the FL as a causal mechanism (albeit an idealized one) of the same nature as the mechanisms which any scientific theory about cognitive architecture attempts to explain. The model in and of itself is not a mechanistic one in that it only specifies the functional properties of its object of description, leaving aside structural properties such as location, temporal order of processing, and the like. Still, the object being described, the FL, can be conceived of as a mechanism. Unlike the advocates of mechanistic explanations,I will argue that there are cognitive mechanisms that can have a genuine functional explanation (i.e. that do not constitute a ‘mechanism sketch’) depending on the correspondence that can be achieved between the cognitive model and the cognitive mechanism. If the correspondence between the entities, activities,and organization postulated by the cognitive model is direct or straightforward regarding the entities, activities, and organization of the mechanism, then there are good chances of obtaining a mechanistic explanation; one in which not only the functional, but also the structural, properties of the mechanism are specified. If, on the other hand, the correspondence is indirect, as in the case of the FL mechanism, the functional explanation appears to be the most adequate to the extent that it highlights the relevant explanatory characteristics of the mechanism.